Hormone Receptor Status and KI67 Proliferation Index in Meningiomas - B, Rajeshwari; Shanmugam, Salapathi; Niamath, Sadiya; Ghosh, Mitra; Ghosh, Siddhartha (Annals of Pathology and Laboratory Medicine, 2020)
Background: Meningiomas are the most common extra-axial tumours of central nervous system arising from arachnoidal cap cells. The biological behaviour of these tumours is unpredictable because of the tendency of these tumours to recur irrespective of the grade. However, WHO grading is the most useful morphological predictor of recurrence. Additional prognostic parameters like Ki67 proliferation index and progesterone receptor status are useful in predicting the risk of recurrence. This study was undertaken to evaluate the spectrum of Ki67 proliferation index in various grades of meningiomas and to correlate these findings with the hormone receptor status. Methods: In this study 225 cases of meningiomas, over 6 yrs period, were studied which included grade 1 and grade 2 meningiomas. The relation between Grade, Ki67 proliferation index and progesterone receptor status was studied. Result: We found a significant positive correlation between grade and Ki67 proliferation index at 0.01 level and significant negative correlation between Grade and progesterone receptor status at 0.05 level. There was also significant negative correlation between progesterone receptor status and Ki67 proliferation index in cases with progesterone receptor staining score of 6 to 12. Many of the grade 1 meningiomas also showed a higher Ki67 proliferation index Conclusion: In this study we conclude that, PR and Ki67 Proliferation index are useful supplements of routine histopathological assessment of meningiomas and can be used as prognostic indicators regarding behavior and response to treatment.